PERANAN LEMBAGA MAHASISWA FAKULTAS USHULUDDIN DAN STUDI ISLAM UINSU DALAM MENANGKAL RADIKALISME DI UINSU - Abdul Halim; Faisal Riza; Febri Ikhsanul Siregar (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
There is an issue of radicalism in Indonesia and the development of current hijrah phenomena that make the college students interested in following it without having to first review who they are studying, worried attitudes, and radicalism entering the campus to attack and change the mindset of students. Radicalism is fanatical to an opinion, permeates the opinions of others, and ignores the welfare of Islam, is not dialogues, likes to disdain other groups of people who disagree, and do textual in understanding religious texts without considering maqasihid al-syari’at (the essence of sharia). This research uses a qualitative approach with a descriptive method that is to decrypt the problem in its entirety as a problem and then analyze the problem. The purpose of this research is to find out the function and role of the Student Institution, the student body's response to radicalism, and the role of the college student institutions in countering radicalism in the Faculty of Ushuluddin and UINSU Islamic Studies. The data was obtained from interviews with several speakers, namely with several DEMA-F and SEMA-F administrators, official websites, journals, and articles. Based on the results of the study, it is known that the college Student Institution's Response to Radicalism in UINSU Fusion is the same continuity and unrest from the board of the college Student Institute of The Faculty of Ushuluddin and UINSU Islamic Studies against radicalism. It should not be taken lightly so that it must be addressed before the wider spread and avoid the onset of unwanted impacts. The role of the college Student Institute of The Faculty of Ushuluddin and Islamic Studies of UINSU in countering Radicalism in the Faculty of Ushuluddin UINSU is to take several steps, among others: to increase the discussion about religious understanding, to conduct studies by presenting Ustadz/Kyai who have clear science and a track record of religious education, mapping, for college  students who appear to have begun to be affected by radicalism, consulted with the Dean/faculty leader, and rejected any activities affiliated with the radicalism movement.Keywords: The role of the college student, Radicalism.